On the formation history of Galactic double neutron stars - Vigna-Gómez, A; Neijssel, CJ; Stevenson, S; Barrett, JW; Belczynski, K; Justham, S; De Mink, SE; Müller, B; Podsiadlowski, P; Renzo, M; Szécsi, D; Mandel, I (Oxford University Press, 2018)
Double neutron stars (DNSs) have been observed as Galactic radio pulsars, and the recent discovery of gravitational waves from the DNS merger GW170817 adds to the known DNS population. We perform rapid population synthesis of massive binary stars and discuss model predictions, including DNS formation rates, mass distributions, and delay time distributions. We vary assumptions and parameters of physical processes such as mass transfer stability criteria, supernova natal kick distributions, remnant mass prescriptions, and common-envelope energetics.We compute the likelihood of observing the orbital period-eccentricity distribution of the Galactic DNS population under each of our population synthesis models, allowing us to quantitatively compare the models.We find that mass transfer from a stripped post-heliumburning secondary (case BB) on to a neutron star is most likely dynamically stable. We also find that a natal kick distribution composed of both low (Maxwellian σ = 30 km s-1) and high (σ = 265 km s-1) components is preferred over a single high-kick component. We conclude that the observed DNS mass distribution can place strong constraints on model assumptions.